Daylily intercropping: Effects on soil nutrients, enzyme activities, and microbial community structure - Gao, Jingxia; Xie, Hua (Frontiers in Plant Science, 2023)
The daylily (Hemerocallis citrina Baroni)/other crop intercropping system can be a specific and efficient cropping pattern in a horticultural field. Intercropping systems contribute to the optimization of land use, fostering sustainable and efficient agriculture. In the present study, high-throughput sequencing was employed to explore the diversity in the root-soil microbial community in the intercropping of four daylily intercropping systems [watermelon (Citrullus lanatus)/daylily (WD), cabbage (Brassica pekinensis)/daylily (CD), kale (Brassica oleracea)/daylily (KD), watermelon/cabbage/kale/daylily (MI)], and determine the physicochemical traits and enzymatic activities of the soil. The results revealed that the contents of available potassium (2.03%-35.71%), available phosphorus (3.85%-62.56%), available nitrogen (12.90%-39.52%), and organic matter (19.08%-34.53%), and the urease (9.89%-31.02%) and sucrase (23.63%-50.60%) activities, and daylily yield (7.43%- 30.46%) in different intercropping soil systems were significantly higher compared to those in the daylily monocropping systems (CK). The bacterial Shannon index increased significantly in the CD and KD compared to the CK. In addition, the fungi Shannon index was also increased significantly in the MI, while the Shannon indices of the other intercropping modes were not significantly altered. Different intercropping systems also caused dramatic architectural and compositional alterations in the soil microbial community. A prominently higher relative richness of Bacteroidetes was noted in MI compared to that in CK, while Acidobacteria in WD and CD and Chloroflexi in WD were pronouncedly less abundant compared to those in CK. Furthermore, the association between soil bacteria taxa and soil characteristic parameters was stronger than that between fungi and soil. In conclusion, the present study demonstrated that the intercropping of daylily with other crops could significantly improve the nutrient levels of the soil and optimize the soil bacterial microflora composition and diversity.